High-viscosity ceramic diaphragm for lithium ion battery and preparation method of high-viscosity ceramic diaphragm

By treating the lithium-ion battery separator with a self-crosslinking network of dopamine hydrochloride and polyethyleneimine, and combining it with a biomimetic mineralization method to prepare a ceramic coating, the problem of weak adhesion of the ceramic coating was solved, and the thermal stability and electrolyte wettability of the separator were improved.

CN119231099AInactive Publication Date: 2024-12-31ZHEJIANG FUNCTIONAL MEMBRANE MATERIAL INNOVATION CENT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411750688.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators, after being coated with ceramic materials, exhibit weak adhesion and poor compatibility, resulting in uneven coating, easy peeling, and impact on thermal stability and thermal conductivity, especially in high-energy and high-power systems.

Method used

Pre-impregnation coating of the membrane substrate with dopamine hydrochloride (DA) was used to form a polydopamine (PDA) modified porous base membrane, which then formed a stable cross-linked network with polyethyleneimine (PEI). Subsequently, a ceramic coating was prepared on the surface by a biomimetic mineralization method to improve adhesion.

Benefits of technology

It enhances the adhesion between the ceramic coating and the diaphragm substrate, improves the thermal stability and electrolyte wettability of the diaphragm, while maintaining good air permeability and mechanical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119231099A_ABST
    Figure CN119231099A_ABST
Patent Text Reader

Abstract

The invention discloses a high-viscosity ceramic diaphragm for a lithium ion battery. The high-viscosity ceramic diaphragm comprises a porous base membrane and a ceramic coating arranged on the surface of the porous base membrane. The porous base membrane is firstly subjected to DA pre-dip-coating treatment to obtain a PDA modified porous base membrane; the ceramic coating comprises a cross-linked network PDA / PEI layer formed by self-crosslinking DA and PEI on the surface of the PDA modified porous base membrane, and a ceramic layer arranged on the PDA / PEI layer through a biomimetic mineralization method. On one hand, the PDA is introduced to improve the binding force between the base film and the coating; the PEI is introduced, and the PEI has high adhesive force and strong reactivity, so that a stable cross-linked PDA / PEI layer can be quickly formed on the surface of the PDA modified diaphragm through Michael addition or Schiff base reaction, and the PDA / PEI layer is strongly attached to the base membrane layer; and on the other hand, the thickness of the ceramic coating formed by adopting the biomimetic mineralization method is small, the influence on the comprehensive performance of the formed membrane is small, and the thermal stability of the diaphragm is further improved through the synergistic effect of the introduced PDA / PEI and the ceramic layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery separators, and in particular to a ceramic separator for a high-viscosity lithium-ion battery and a preparation method thereof. Background Art

[0002] Lithium-ion battery separators play a vital role in maintaining the long-cycle cycle and high-rate charge and discharge performance of batteries, and their heat resistance directly affects the safety and stability of the battery. At present, the most commonly used method to solve the problem of poor thermal stability of the separator is to coat or graft on the surface of the separator, that is, to introduce heat-resistant inorganic or organic materials on the surface of the separator. This method uses a protective layer composed of heat-resistant materials to improve the heat resistance of the separator itself, avoid the occurrence of thermal shrinkage, effectively improve thermal stability, improve the shrinkage resistance of the separator, and reduce the risk of short circuit. For example, SiO2, Al2O3, ZrO2, TiO2 and other inorganic ceramic materials are added to modify the separator. The inorganic ceramic powder is distributed on the surface of the separator in the form of a continuous phase and anchored on the base material, which effectively inhibits the thermal shrinkage of the polyolefin separator, so that the separator has good thermal stability, high mechanical stability and relatively high thermal conductivity.

[0003] However, there are certain defects in directly coating ceramic materials on the surface of the diaphragm. For example, the bonding force between the ceramic material and the diaphragm is weak and difficult to maintain stably for a long time. Therefore, adhesives are used to enhance the interaction between the inorganic material and the diaphragm and improve the adhesion of the ceramic material. In addition, the poor compatibility of inorganic particles with the organic phase, the complex and uneven dispersion of the slurry components result in uneven coating, or the weak connection between the coating and the substrate can easily cause insufficient bonding between the material and the diaphragm, resulting in particle shedding, thereby reducing thermal stability; in addition, the increase in thickness caused by the accumulation of coating particles can also cause partial pore blockage, affecting their application, especially in high-energy and high-power systems. For example, CN118117258A discloses a ceramic diaphragm for lithium-ion batteries and a preparation method thereof, which specifically includes a porous base membrane and a ceramic coating coated on at least one side of the porous base membrane, wherein the ceramic coating includes modified nanoporous ceramics, a dispersant, a thickener, a composite binder and a surfactant, wherein, in order to enhance the compatibility of inorganic particles with the organic phase, the modified nanoporous ceramics have a complex treatment process, including corrosion, activation and nanocellulose modification; the composite binder is a mixture of dopamine hydrochloride and an aqueous binder. Generally speaking, the slurry ratio has more components and the process is complicated.

[0004] Based on the above problems, the present invention discloses a high-viscosity ceramic diaphragm for lithium-ion batteries, which has a simple preparation process, is environmentally friendly, and has a ceramic coating with strong adhesion. At the same time, the diaphragm has excellent electrolyte wettability and thermal stability. Summary of the invention

[0005] The object of the present invention is to provide a high-adhesion ceramic diaphragm for lithium-ion batteries and a preparation method thereof. First, dopamine hydrochloride (DA) is used to pre-dip coat the diaphragm substrate to obtain a polydopamine (PDA) modified porous base membrane, and then DA and polyethyleneimine (PEI) are self-crosslinked to form a stable cross-linked network PDA / PEI layer on the surface of the PDA modified porous base membrane. Finally, a ceramic coating is prepared on the PDA / PEI layer by a bionic mineralization method to obtain a high-adhesion ceramic diaphragm for lithium-ion batteries with in-situ deposition of ceramic particles.

[0006] In one aspect, the present invention provides a high-adhesion ceramic separator for lithium-ion batteries, comprising a porous base membrane and a ceramic coating disposed on the surface of the porous base membrane.

[0007] The material of the porous base film includes any one or more of PE film, PP film, PI film, PET film, PP / PE film, PP / PE / PP film, and the thickness of the porous base film is 5-25 μm; Preferably, the porous base film is a PE film, a PP film or a PET film.

[0008] Furthermore, the porous base membrane is first subjected to DA-modified pre-impregnation treatment to obtain a PDA-modified porous base membrane; Specifically, the PDA-modified porous base membrane is obtained by immersing the porous base membrane in a DA solution (10 mM) with methanol and Tris buffer (pH 8.5) as a co-solvent (methanol:Tris buffer = 1:1 by volume), taking it out after immersion for 2 to 8 hours, rinsing it with water, and drying it under argon protection.

[0009] The ceramic coating comprises a PDA / PEI layer formed by self-crosslinking of DA and PEI on the surface of a PDA-modified porous base film to form a stable crosslinked network, and a ceramic layer arranged on the PDA / PEI layer by a bionic mineralization method.

[0010] Further, in some embodiments of the present invention, the biomimetic mineralization method refers to treating a porous base membrane (PDA / PEI-X) with a PDA / PEI layer by dip coating with a zirconium (IV) sulfate tetrahydrate (Zr(SO4)2·4H20) solution, thereby forming a ZrO2 ceramic layer on the PDA / PEI layer; The biomimetic mineralization method is based on the chelation of ZrO2 from Zr(SO4)2·4H2O solution by the catechol groups on the PDA / PEI layer, thereby forming a ZrO2 ceramic layer.

[0011] Further, in some embodiments of the present invention, the biomimetic mineralization method refers to treating a porous base membrane (PDA / PEI-X) with a PDA / PEI layer with a dipping treatment of aluminum sulfate (III) tetrahydrate (Al2(SO4)3·4H2O) solution, thereby forming an Al2O3 ceramic layer on the PDA / PEI layer; The biomimetic mineralization method is based on the chelation of Al2O3 from Al2(SO4)3·4H2O solution by the catechol groups on the PDA / PEI layer, thereby forming an Al2O3 ceramic layer.

[0012] The present invention provides a method for preparing a high-viscosity ceramic diaphragm for a lithium-ion battery, comprising the following preparation steps: Step 1: Preparation of PDA-modified porous base membrane (PDA-X) treated with DA pre-impregnation The porous substrate membrane was immersed in a DA solution (10 mM) with methanol and Tris buffer (pH 8.5) as co-solvents, wherein methanol:Tris buffer = 1:1, and taken out after immersion for 2 to 8 hours to obtain a PDA-X porous substrate membrane, which was rinsed with water 1 to 2 times and dried under argon protection for later use; The porous base film is any one or more of a PE film, a PP film, a PI film, a PET film, a PP / PE film, and a PP / PE / PP film, and the thickness of the porous base film is 5-25 μm.

[0013] Step 2: Setting up the cross-linked network PDA / PEI layer The pre-impregnated PDA-X porous substrate obtained in step 1 was pre-wetted with ethanol, then immersed in a mixed solution of DA and PEI with Tris-HCl buffer solution (50 mM, pH 8.5) as solvent, and finally gently shaken for 4 h, wherein DA and PEI were dissolved in a mass ratio of 1:1, and their concentrations were 2 g•L -1 ; The porous membrane was then washed with deionized water and finally dried in vacuum at 60°C for 12 h to obtain a PDA / PEI-X porous base membrane with a cross-linked network PDA / PEI layer.

[0014] Step 3: Setting of ceramic coating Add Zr(SO4)2·4H2O or Al2(SO4)3·4H2O to HCl solution (10 mM) and stir magnetically for half an hour to completely dissolve it to form a solution with a concentration of 0.1 g·L -1 ~0.5 g•L -1The PDA / PEI-X porous base membrane obtained in step 2 is then immersed in the above-configured Zr(SO4)2·4H2O or Al2(SO4)3·4H2O HCl aqueous solution at 25°C for 8 h, washed with deionized water 5 to 6 times, and vacuum dried at 60°C for 12 h to obtain a high-viscosity ceramic separator for lithium-ion batteries.

[0015] Compared with the prior art, the high-viscosity ceramic diaphragm for lithium-ion batteries provided by the present invention has at least the following beneficial effects: 1. The present invention introduces polydopamine to improve the bonding force between the diaphragm base film and the coating, and the bonding force between the PDA-modified substrate and the ceramic coating is extremely strong, which greatly reduces the possibility of the ceramic coating falling off; 2. The introduction of polyethyleneimine, because PEI has high adhesion and strong reactivity, and its main chain is rich in amino groups, can quickly form a stable cross-linked PDA / PEI layer on the surface of the PDA-modified porous base membrane treated with DA pre-dip coating through Michael addition or Schiff base reaction, and strongly adhere to the base membrane layer; 3. The ceramic layer was prepared by the biomimetic mineralization method. The catechol groups on the PDA / PEI layer synergistically acted with the highly adsorbent PEI to chelate ZrO2 from the Zr(SO4)2·4H2O solution, thereby forming a ZrO2 ceramic layer. The introduced PDA / PEI and ZrO2 coatings can further improve the thermal stability of the diaphragm. The ceramic coating formed based on the biomimetic mineralization method has a small thickness and has little effect on the comprehensive performance of the film. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the structure of a high-viscosity ceramic diaphragm for lithium-ion batteries.

[0017] Figure 2 Schematic diagram of the cross-sectional structure of a high-viscosity ceramic diaphragm for lithium-ion batteries.

[0018] 1——porous base film layer; 2——PDA / PEI layer; 3——ceramic layer; 4——ceramic coating DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0020] Among them, zirconium sulfate tetrahydrate (Zr(SO4)2·4H2O) and aluminum sulfate (III) tetrahydrate (Al2(SO4)3·4H2O) were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd.; dopamine hydrochloride (DA), tris(hydroxymethyl)aminomethane (Tris buffer solution), hydroxytyrosol (HT), and polyvinyl alcohol (PVA, Mw = 9000-10000) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; polyethyleneimine (PEI, Mw = 600 Da) was purchased from Shanghai Aladdin Reagent Co., Ltd. All reagents were analytical grade.

[0021] Example 1 A high-viscosity ceramic diaphragm for lithium-ion batteries, comprising a porous base film and a ceramic coating disposed on the surface of the porous base film, such as Figure 1 As shown; The porous base film is a PE film with a thickness of 15 μm; The PE membrane is firstly treated with DA pre-impregnation to obtain a PDA-modified porous base membrane, i.e., a PDA-PE porous base membrane; The ceramic coating comprises a PDA / PEI layer formed by self-crosslinking of DA and PEI on the surface of a PDA-PE porous base film layer to form a stable crosslinked network, and a ceramic layer arranged on the PDA / PEI layer by a bionic mineralization method. Figure 2 The specific preparation steps are as follows: Step 1: Preparation of PDA-modified porous membrane (PDA-PE) treated with DA pre-impregnation The PE porous base membrane was immersed in a DA solution (10 mM) with methanol and Tris buffer (50 mM, pH 8.5) as co-solvents, wherein methanol:Tris buffer = 1:1 by volume. After soaking for 2 h, it was taken out to obtain a PDA-PE membrane, which was rinsed once with water and dried under argon protection for later use.

[0022] Step 2: Setting up the cross-linked network PDA / PEI layer The pre-impregnated PDA-PE porous substrate obtained in step (1) was pre-wetted with ethanol and then immersed in 100 mL of a mixed Tris-HCl buffer solution (50 mM, pH 8.5) of DA and PEI. Finally, it was gently shaken for 4 h, in which DA and PEI were dissolved in a mass ratio of 1:1, and their concentrations were 2 g·L -1 Then, it was washed with deionized water once and finally dried under vacuum at 60 °C for 12 h to obtain a PDA / PEI-PE porous base membrane.

[0023] Step 3: Ceramic layer setting 300 mg Zr(SO4)2•4H2O was added to 100 mL HCl solution (10 mM) and magnetically stirred for half an hour to completely dissolve it. Then, the PDA / PEI-PE porous base membrane was immersed in the HCl solution of Zr(SO4)2 at 25 °C for 8 h. The obtained membrane was washed with deionized water for 5 to 6 times and vacuum dried at 60 °C for 12 h to obtain the ZrO2–PDA / PEI–PE1 membrane.

[0024] Example 2 As provided in Example 1, a high-viscosity ceramic diaphragm for lithium-ion batteries, in the preparation process of the PDA-modified porous membrane treated with DA pre-impregnation treatment in step 1, the PE diaphragm is immersed in a mixed solution of methanol / Tris buffer for 5 h, and the other steps remain unchanged to obtain a ZrO2-PDA / PEI-PE2 diaphragm.

[0025] Example 3 For a ceramic diaphragm as provided in Example 1, in the preparation process of the PDA modified porous membrane treated with DA pre-impregnation treatment in step 1, the PE diaphragm is immersed in the mixed solution of methanol / Tris buffer for 8 hours, and the other steps remain unchanged to obtain a ZrO2-PDA / PEI-PE3 diaphragm.

[0026] Example 4 For a ceramic diaphragm as provided in Example 1, during the setting of the ceramic layer in step three, Zr(SO4)2·4H2O is replaced by Al2(SO4)3·4H2O, and the remaining steps remain unchanged to obtain an Al2O3-PDA / PEI-PE diaphragm.

[0027] Example 5 For a ceramic diaphragm as provided in Example 2, during the setting of the ceramic layer in step three, the amount of Zr(SO4)2•4H2O is adjusted to 100 mg, and the remaining steps remain unchanged to obtain a ZrO2–PDA / PEI–PE4 diaphragm.

[0028] Example 6 For a ceramic diaphragm as provided in Example 2, during the setting of the ceramic layer in step three, the amount of Zr(SO4)2•4H2O is adjusted to 500 mg, and the remaining steps remain unchanged to obtain a ZrO2–PDA / PEI–PE5 diaphragm.

[0029] Comparative Example 1 A ceramic diaphragm as provided in Example 1 does not include step 1, that is, the PE porous membrane is not pre-impregnated with DA, and the other steps remain unchanged to obtain a ZrO2-PDA / PEI-PE0 diaphragm.

[0030] Comparative Example 2 For a ceramic diaphragm as provided in Example 2, the DA in step one and step two is replaced by hydroxytyrosol (HT), and the other steps remain unchanged to obtain a ZrO2-HT / PEI-PE diaphragm.

[0031] Comparative Example 3 For a ceramic diaphragm as provided in Example 2, the DA in step one and step two is replaced with polyvinyl alcohol (PVA), and the other steps remain unchanged to obtain a ZrO2-PVA / PEI-PE diaphragm.

[0032] Comparative Example 4 A diaphragm as provided in Example 2 does not include step two and step three, that is, only DA pre-impregnation treatment is performed to obtain a PDA-PE diaphragm.

[0033] Comparative Example 5 For a ceramic diaphragm as provided in Example 2, the PEI in step 2 is replaced by DA, and the other steps remain unchanged to obtain a ZrO2-PDA-PE diaphragm.

[0034] Comparative Example 6 A ceramic diaphragm as provided in Example 2 does not include step 1, and DA in step 2 is replaced by PEI, while the other steps remain unchanged to obtain a ZrO2-PEI-PE diaphragm.

[0035] Comparative Example 7 A ceramic diaphragm as provided in Example 4 does not include step 1, and DA in step 2 is replaced by PEI, while the other steps remain unchanged to obtain an Al2O3-PEI-PE diaphragm.

[0036] Comparative Example 8 A ceramic diaphragm as provided in Example 2 does not include step three, that is, is not treated with a Zr(SO4)2•4H2O solution to obtain a PDA / PEI–PE diaphragm.

[0037] Comparative Example 9 A PE diaphragm as provided in Example 2 without any treatment.

[0038] The performance of the diaphragms prepared in Examples 1-6 and Comparative Examples 1-9 was tested in the following manner, and the data results are shown in Table 1: (1) Air permeability test: The test is carried out according to the test method for air permeability in the national standard "GB / T-36363-2018". The results of air permeability are expressed by Gurley value. The smaller the Gurley value, the shorter the time for gas to pass through, and the better the air permeability of the membrane; (2) Heat resistance test: The heat shrinkage rate is used to characterize the heat resistance of the diaphragm. The test is carried out according to the test method for heat shrinkage rate in the national standard "GB / T-36363-2018". The instrument uses a blast oven; (3) Tensile strength test: Test according to the tensile strength test method in the national standard "GB / T-36363-2018"; (4) Electrolyte wettability test: The wettability of the diaphragm to the electrolyte is tested by contact angle: Contact angle test: drop 10 μL of electrolyte on the surface of the diaphragm and record the angle between the electrolyte and the diaphragm. The smaller the angle, the better the electrolyte spreads on the diaphragm surface and the stronger the affinity between the two. (5) Ionic conductivity test: The bulk resistance was tested by assembling steel sheet / diaphragm / steel sheet using the electrochemical impedance spectroscopy (EIS) mode of a VMP3B-10 electrochemical workstation (Bio-Logic Science Instruments), where the disturbance voltage amplitude was 5 mV and the frequency was 10 mHz to 1 MHz. The relationship between bulk resistance and ionic conductivity is: ionic conductivity = diaphragm thickness / (diaphragm resistance*contact area between diaphragm and electrode)*10 -2 , where the unit of diaphragm thickness is mm, the unit of diaphragm resistance is Ω, and the unit of contact area between diaphragm and electrode is m2; (6) Peel strength test: The test is conducted according to the method in the national standard "GB / T 2792-2014 Peel strength of adhesive tapes", and the instrument used is a universal material testing machine.

[0039] Table 1 Summary of the test results of battery separator performance prepared in Examples 1-6 and Comparative Examples 1-9

[0040] It can be seen from the data in Table 1 that compared with Comparative Example 9, i.e., the untreated PE diaphragm, the diaphragms prepared by Examples 1-2, 4, and 5-6 of the present invention have a small contact angle, excellent electrolyte wettability, and a low heat shrinkage rate, and have good thermal stability and high air permeability, indicating that the setting of the coating does not damage the pores of the base film; in addition, it has good tensile strength and ionic conductivity. At the same time, the peel strength of the coating is high, indicating that the coating has good adhesion performance.

[0041] From the comparison of Examples 1-3 and Comparative Example 1, it can be seen that the pre-impregnation treatment of PE porous membrane with DA will affect the performance of the finished diaphragm. If the DA treatment time is too long, the air permeability of the diaphragm will deteriorate. It may be that too much DA penetrates into the interior of the diaphragm layer and the degree of polymerization is high, and then forms a relatively dense cross-linked network with the subsequent PDA / PEI, and finally forms a ceramic coating, causing some pores on the surface of the diaphragm to be damaged; however, the PE porous membrane is not pre-impregnated with DA, and the peel strength of the obtained diaphragm coating is poor, indicating that the adhesion between the ceramic coating and the base membrane layer is insufficient.

[0042] In addition, by comparing Example 2 with Comparative Examples 2, 3 and 6-8, it can be found that the introduction of DA, on the one hand, significantly improves the bonding force between the diaphragm and the ceramic layer, and on the other hand, the introduction of DA improves the heat resistance of the diaphragm. Although polyvinyl alcohol is also a binder, and hydroxytyrosol has a similar structure to dopamine, it is not as effective as DA in terms of bonding and improving film heat resistance. This may be because, on the one hand, dopamine can form a polymer that strongly adheres to the base film layer, and at the same time, the PEI main chain is rich in amino groups. Through Michael addition or Schiff base reaction, a stable cross-linked PDA / PEI layer can be quickly formed on the surface of the PDA-PE base film layer, thereby improving the bonding between the coating and the base film layer; on the other hand, the catechol group on the PDA / PEI layer chelates ZrO2 from the Zr(SO4)2 solution to form a ZrO2 coating. The introduced PDA / PEI and ZrO2 coating work synergistically to further improve the thermal stability of the diaphragm.

[0043] By comparing Example 2 with Comparative Examples 4 and 5, it can be found that the introduction of PEI is also effective in improving the heat resistance of the finished diaphragm, which may be due to the adsorption of PEI on ceramic particles, enhancing the chelating effect of PDA / PEI on ZrO2; in addition, by comparing Example 2 with Example 4, it can be found that in terms of heat resistance, the treatment effect of Zr(SO4)2 aqueous solution is better than that of Al2(SO4)3, which may be due to the stronger ability of zirconium (IV) to chelate with catechol groups in solution to form ZrO2, and the obtained ZrO2 ceramic layer is more dense and orderly.

Claims

1. A high-viscosity ceramic separator for lithium-ion batteries, comprising a porous base membrane and a ceramic coating disposed on the surface of the porous base membrane, characterized in that: The porous base membrane is first subjected to a dopamine-modified pre-impregnation treatment to obtain a polydopamine-modified porous base membrane; The ceramic coating comprises a cross-linked network polydopamine / polyethyleneimine layer formed by self-crosslinking dopamine and polyethyleneimine on the surface of a polydopamine-modified porous base film, and a ceramic layer disposed on the polydopamine / polyethyleneimine layer by a biomimetic mineralization method; The ceramic layer is a ZrO2 or Al2O3 ceramic layer; The bionic mineralization method refers to subjecting the porous base membrane with the polydopamine / polyethyleneimine layer to a dipping treatment with a Zr(SO4)2•4H2O or Al2(SO4)3•4H2O solution, thereby forming a ZrO2 or Al2O3 ceramic layer on the polydopamine / polyethyleneimine layer.

2. A high-viscosity ceramic diaphragm for lithium-ion batteries according to claim 1, characterized in that: The material of the porous base film includes any one or more of PE film, PP film, PI film, PET film, PP / PE film, PP / PE / PP film, and the thickness of the porous base film is 5-25 μm.

3. A high-viscosity ceramic diaphragm for lithium-ion batteries according to claim 2, characterized in that: The polydopamine modified porous base membrane is obtained by immersing the porous base membrane in a dopamine solution with a concentration of 10 mM, which uses methanol and Tris buffer with a pH of 8.5 as co-solvents, wherein the methanol:Tris buffer = 1:1 by volume, soaking for 2 to 8 hours, taking it out, rinsing it with water, and drying it under argon protection.

4. A high-viscosity ceramic diaphragm for lithium-ion batteries according to claim 3, characterized in that: The biomimetic mineralization method is based on the chelation of ZrO2 or Al2O3 by the catechol groups on the polydopamine / polyethyleneimine layer from Zr(SO4)2•4H2O or Al2(SO4)3•4H2O solution to form a ZrO2 or Al2O3 ceramic layer.

5. The method for preparing a high-viscosity ceramic diaphragm for lithium-ion batteries according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: Step 1: Preparation of polydopamine modified porous base membrane treated with dopamine pre-impregnation coating: The porous base membrane is immersed in a dopamine solution with methanol and Tris buffer as co-solvents, and taken out after immersion for 2 to 8 hours to obtain a polydopamine modified porous base membrane, which is then rinsed with water and dried under argon protection for later use; Step 2: Setting of cross-linked network polydopamine / polyethyleneimine layer: The pre-impregnated polydopamine-modified porous base membrane obtained in step 1 was pre-wetted with ethanol, then immersed in a mixed solution of dopamine and polyethyleneimine using a Tris-HCl buffer solution as a solvent, shaken for 4 hours, then washed with deionized water, and finally vacuum dried to obtain a polydopamine / polyethyleneimine-X porous base membrane with a cross-linked network polydopamine / polyethyleneimine layer; Step 3. Setting of ceramic coating: Add Zr(SO4)2•4H2O or Al2(SO4)3•4H2O to HCl solution, stir magnetically for half an hour, then soak the polydopamine / polyethyleneimine-X porous base membrane obtained in step 2 in the above-configured Zr(SO4)2•4H2O or Al2(SO4)3•4H2O HCl aqueous solution at 25°C for 8 h, wash with deionized water 5 to 6 times, and vacuum dry to obtain a ceramic diaphragm.

6. The method for preparing a high-viscosity ceramic diaphragm for lithium-ion batteries according to claim 5, characterized in that: In the step 1, the ratio of the methanol and Tris buffer co-solvent is, by volume, methanol:Tris buffer = 1:1; the concentration of the dopamine solution is 10 mM, and the pH of the Tris buffer is 8.

5.

7. The method for preparing a high-viscosity ceramic diaphragm for lithium-ion batteries according to claim 6, characterized in that: In step 2, the concentration of the Tris-HCl buffer solution is 50 mM and the pH is 8.5; the mass ratio of dopamine and polyethyleneimine is 1:1 and the concentrations are 2 g·L -1 .

8. The method for preparing a high-viscosity ceramic diaphragm for lithium-ion batteries according to claim 7, characterized in that: In the step 3, the concentration of the HCl solution is 10 mM; in the step 2 or step 3, the vacuum drying temperature is 60° C. and the time is 12 h.

9. The method for preparing a high-viscosity ceramic diaphragm for lithium-ion batteries according to claim 8, characterized in that: In step 3, the concentration of the Zr(SO4)2•4H2O or Al2(SO4)3•4H2O solution is 0.1 g•L -1 ~0.5 g•L -1 .

10. The method for preparing a high-viscosity ceramic diaphragm for lithium-ion batteries according to claim 9, characterized in that: The porous base film is any one or more of a PE film, a PP film, a PI film, a PET film, a PP / PE film, and a PP / PE / PP film, and the thickness of the porous base film is 5-25 μm.

Citation Information

Patent Citations

  • Pretreatment method based on silica sol ceramic diaphragm

    CN103554549A

  • Lithium ion battery separator containing poly-dopamine and ceramic coatings

    CN103682216A

  • Preparation method of heat-resistant lithium ion battery diaphragm

    CN110611069A

  • SiO2-polyolefin lithium battery composite diaphragm and preparation method thereof

    CN114566761A

  • Separator for lithium secondary battery and method for manufacturing same

    CN115207557A